Structural Analysis of Carbapenems and β-Lactamase Resistance - Hayder Kadhim Sunaid (Academia Open, 2025)
General Background: Carbapenem antibiotics represent a critical class of β-lactam agents widely used to manage severe infections caused by multidrug-resistant bacteria. Specific Background: Their unique structure—particularly the carbon substitution at C-1 and the C2–C3 double bond—confers exceptional stability against β-lactamase-mediated hydrolysis. Knowledge Gap: However, the molecular determinants that govern their interaction with penicillin-binding proteins and resistance to β-lactamases remain insufficiently explained. Aims: This study analyzes the structural characteristics of carbapenems and explains how these features relate to bacterial β-lactamase resistance. Results: Findings show that core structural modifications strengthen carbapenem binding to PBPs, disrupt peptidoglycan cross-linking, and maintain activity against extended-spectrum and metallo-β-lactamase-producing bacteria. Novelty: The work synthesizes current structural–activity insights to clarify how specific molecular configurations preserve carbapenem potency. Implications: These insights support rational drug design for next-generation carbapenems capable of combating emerging resistance threats within clinical settings. Highlights: Structural features of carbapenems determine stability against β-lactamases. Binding to PBPs remains central to their bactericidal activity. Findings support future development of improved carbapenem derivatives. Keywords: Carbapenem, β-Lactamase, Molecular Structure, Antibiotic Resistance, PBPs